ON SOME GENERALIZED DEFERRED STATISTICAL CONVERGENCE OF ORDER αβ FOR FUZZY VARIABLE SEQUENCES IN CREDIBILITY SPACE - Sava, Ekrem; Kişi, Ömer; Gurdal, Mehmet; Kişi, Ömer (Univ Nis, 2023)
In this paper, we investigate the concepts of deferred statistical convergence of order alpha beta and strongly s-deferred Cesaro summability of order alpha beta for fuzzy variable sequences in credibility space. Furthermore, the conditions of deferred statistical convergence almost surely of order alpha beta, deferred statistical convergence in credibility of order alpha beta, deferred statistical convergence in mean of order alpha beta, deferred statistical convergence in distribution of order alpha beta, and deferred statistical convergence uniformly almost surely of order alpha beta of fuzzy variable sequences have been examined. We have proved relations between these notions.
Keywords: Statistical Convergence; Deferred Statistical Convergence; Fuzzy Variable Sequences